IMPLEMENTASI APLIKASI ONLINE SURAT KETERANGAN PENDAMPING IJAZAH - Teri Mengkasrinal, Efmi Maiyana (Menara Ilmu, 2018)
The use of Diploma Supplement (SKPI in Indonesian Term) is crucial nowadays in order toknow the quality of graduate student produced, this is supported by occuring government’srules number 81 year 2014 section 1st part 4th about Certificate, Profession Certificate, andUniversity Competence Certificate which states Certificate of Accompanying Diploma/SKPIin Indonesian Term/Diploma Supplement in English Term is a kind of document containingacademic achievement information or qualification of titled higher education, therefore, it isexpected may produced qualified graduate students who can be accepted in the society and fortheir future career. However, based on survey result, there are still many universities have notused yet diploma supplement recently, whereas the universities which have used diplomasupplement is still manual or uncomputerized yet in database program, therefore they facedifficulty in searching datas or processing datas of this diploma suppelement. To solve thisproblem there has been done such programme of web-android based information system, theresearch done by research and development technique. By using this method, it is expectedmay produced proven products and may access online implementation by applying SDLC(System Development Life Cycle) as a model of this research. The implementation of onlineapplication of diploma supplement/SKPI is expected simply used by all users, universitystudents or academic part, as a result it can be easier to make it real the purpose of developingits diploma supplemet/SKPI.Keywords : SKPI(Diploma Supplement, implementation, online, SDLC